Fixed rules of play for dividing up the Arctic Ocean: The Ilulissat Declaration of the Arctic Coastal States - Winkelmann, Ingo (Berlin: Stiftung Wissenschaft und Politik (SWP), 2008)
At the end of May 2008 the five countries bordering on the Arctic - Denmark, Canada, Norway, the Russian Federation and the United States of America (known as the 'A5') - adopted a carefully-worded declaration. Known as the Ilulissat Declaration after the place in Greenland where the conference was held, it outlines the kind of co-operation the A5 is considering. From the text one can also glean what principles will be applied regarding legal arrangements, research, managing natural resources and the ecosystem of the Arctic Ocean. In the declaration the A5 emphasise their supremacy in this area. They speak in favour of applying the international law of the sea to the Arctic but against the conclusion of a specific Arctic agreement. This sends an important signal to other potential Arctic players and to the international community, and is therefore also of interest to Germany, which for environmental, research and economic reasons cannot be indifferent to the Arctic region